THE ROLE OF INDUSTRIAL PSYCHOLOGY IN HUMAN RESOURCES MANAGEMENT IN THE ERA OF SOCIETY 5.0 - Purwani, Widio (KOMITMEN: Jurnal Ilmiah Manajemen, 2023)
The emergence of the Covid-19 pandemic has harmed many companies. But apart from the company, employees as human entities also experience various problems, such as stress. Industrial psychology is then present to help understand the impacts that occur in society. This study then aims to see the role of industrial psychology in the era of Society 5.0. This research will use a qualitative approach. The research data comes from the results of previous research and studies which still have relevance to the contents of this study. The results of this study then found that the market will always continue to grow to remain efficient and effective. The emergence of a pandemic that has destroyed many industrial sectors requires a new strategy. Industrial psychology is present and actively plays a role in developing human resource management in the Society 5.0 era. Through the presence of industrial psychology, it is hoped that human resources will survive well even though the dynamics of the industrial world continue to change.